Outcome of Respiratory Failure Patients Managed In Medical Intensive Care Units (ICUs) - Mahreen Zia, Maria Arif , Muhammad Khurram (Journal of Rawalpindi Medical College, 2018)
Background: To find out the outcome of patients managed with diagnosis of respiratory failure at Medical ICUs Methods: In this cross sectional observational study all respiratory failure patients managed at Medical ICUs were included. Data regarding patient characteristics, cause and type of respiratory failure (type I or II), outcome (improved or expired) and duration of hospitalization was collected for each patient. Outcome was correlated with age, gender, hospital, cause and type of respiratory failure and duration of hospitalization employing Chi2 or t test wherever appropriate. p- value <0.05 was considered significant. Results: Two hundred and forty eight patients were included. 61.69% were male. Mean patient age was 48.58± 18.81 years. Type I respiratory failure was noted in 58.46% and type II respiratory failure in 41.53%. Chronic obstructive pulmonary disease, pneumonia and tuberculosis were commonest causes of respiratory failure. Mean duration of hospitalization was 4.69± 7.75 days. 57.25% patients expired and 42.74% recovered. Statistical association of outcome was only noted with difference to two hospitals. Conclusion: Poor outcome is noted in majority respiratory failure patients . Chronic obstructive airway disease (COPD), pneumonia and pulmonary tuberculosis (TB) related lung damage are commonest etiologies of respiratory failure in these patients.